Enriqueta Zuloaga's claim as a tool to approach the study of the role of the Topographic Department of Mendoza in the government of the territory (1867). (Res Gesta, 2021)
In April 1867 a neighbor of the City of Mendoza, Enriqueta Zuloaga, sent a letter to the governor of Mendoza questioning the way in which José Galigniana, surveyor and director of the Topographic Department, had made the delineation of her land requesting the intervention of various authorities in order for their conflict to be resolved. This work aims to be an approximation to the role of that office and of the surveyors in the government of the provincial territory, of their relationship with the neighbors and with other agents and agencies of the provincial State. For this, two theoretical axes are followed: the first, linked to the knowledge of the history of Mendoza in the 1860s and of the political, social and economic reality of the province, together with the relevance that the Topographic Department had within the local administration, and the second, is related to the field of study of the State and its agencies within which framework the formation of this public office in Mendoza will be addressed.
Keywords: State agencies; Topographic Department; Mendoza